Analysis of Internal Control System In Granting Credit In Pt. Bank Mandiri KCP Medan Belawan - Yosy Meliyana Batubara; Anggi Pratama (Rowter Journal, 2022)
This study aims to analyze the internal control system in providing credit at pt. Bank Mandiri KCP Medan Belawan and what actions were taken by the relevant departments in overcoming fluctuations in total credit, gross NPL, net NPL, and the ratio of core debtors to total credit at PT. Bank Mandiri (Persero) Tbk. 2016-2020 so as to be able to fulfill the entire process of providing credit without compromising the internal control system. This research was conducted using a descriptive method. Data collection techniques were carried out by means of interviews, studying documents and records about the company through the collection of information sourced from primary and secondary data. The results of the research on analysis, in distributing credit, Bank Mandiri always prioritizes the principle of prudence by placing the credit analysis function carried out by an independent business unit and credit risk unit. Bank Mandiri is always guided by the Credit Policy (KPKD) in managing end-to-end credit risk. Operationally, this policy is set forth in the form of Standard Credit Procedures (SPK) and Product Manuals. To speed up the process and improve credit performance, Bank Mandiri KCP Medan Belawan has also set limits on its authority to make credit decisions based on credit exposure and risk level. The greater the exposure, the greater the quorum of authority holders, consisting of members of the Credit Committee who function as Risk Management and members of the Credit Committee who function as Business Units. The internal control system implemented by Bank Mandiri KCP Medan Belawan is considered to have been running effectively and adequately reflected in the effectiveness of the implementation of internal control functions, including internal audit, risk management, compliance and operational control functions. In disbursing credit, PT Bank Mandiri (Persero) KCP Medan Belawan first conducts a search on customer data or prospective customers who will apply for credit based on certain procedures. Employees of PT Bank Mandiri (Persero) KCP Medan Belawan have carried out their duties in accordance with the responsibilities given.